2017
DOI: 10.1038/nature23291
|View full text |Cite
|
Sign up to set email alerts
|

Tumours with class 3 BRAF mutants are sensitive to the inhibition of activated RAS

Abstract: Approximately 200 BRAF mutant alleles have been identified in human tumours. Activating BRAF mutants cause feedback inhibition of GTP-bound RAS, are RAS-independent and signal either as active monomers (class 1) or constitutively active dimers (class 2)1. Here we characterize a third class of BRAF mutants—those that have impaired kinase activity or are kinase-dead. These mutants are sensitive to ERK-mediated feedback and their activation of signalling is RAS-dependent. The mutants bind more tightly than wild-t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

28
558
1
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 428 publications
(589 citation statements)
references
References 18 publications
28
558
1
2
Order By: Relevance
“…This is the first example of a lineage dependent mechanism of acquired resistance and is due either to the higher level of RTK signaling in CRC than in melanoma or to the increased sensitivity of RTK signaling to ERK-dependent feedback in melanoma compared to CRC. We have recently shown that hypoactive BRAF mutants serve a similar function(32, 33). They amplify ERK signaling in a RAS-dependent manner and, in lung and colon carcinomas, cooperate with upstream RTKs to drive transformation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is the first example of a lineage dependent mechanism of acquired resistance and is due either to the higher level of RTK signaling in CRC than in melanoma or to the increased sensitivity of RTK signaling to ERK-dependent feedback in melanoma compared to CRC. We have recently shown that hypoactive BRAF mutants serve a similar function(32, 33). They amplify ERK signaling in a RAS-dependent manner and, in lung and colon carcinomas, cooperate with upstream RTKs to drive transformation.…”
Section: Discussionmentioning
confidence: 99%
“…They amplify ERK signaling in a RAS-dependent manner and, in lung and colon carcinomas, cooperate with upstream RTKs to drive transformation. Interestingly, levels of RAS-GTP in melanomas are also not sufficient to cooperate with low activity RAF mutations(33). Tumors with these mutations are invariably found to coexist with NF1 inactivation or RAS mutations.…”
Section: Discussionmentioning
confidence: 99%
“…The maximal tumor responses for patients with BRAF non-V600 mutations ( n = 28) are shown in Fig. 4C and are classifi ed by their kinase activity ( 12,40 ). Of note, central nervous system (CNS) responses were seen in a patient with BRAF V600E-mutant lung cancer with metastases, and another with BRAF V600E-mutant glioblastoma mulitforme.…”
Section: Dose-expansion Cohortsmentioning
confidence: 99%
“…These factors are likely to include allele-specific attributes of oncogenic mutations in genes such as KRAS 36 and BRAF [36][37][38] ; the cell lineage in which the cancer has arisen 22,37,39 ; the levels of expression of mutant cancer genes 32,38,40,41 ; the co-existence of certain additional mutations 42 ;…”
Section: Discussionmentioning
confidence: 99%